Is there a correlation of the asymmetry among the three thirds of the face?. (October 2021) - Granucci, M.; Chabot, P.; Sales, S.; Reis, S.; Campos, F.
Abstract : Introduction: Facial asymmetry (FA) is a well-described condition with a high global incidence that negatively impacts individuals functionally and aesthetically. Besides the higher incidence of FA, there is still a lack of knowledge about the etiology and clinical classification in scientific literature. The current most used classifications are based on 2-D methodology and specific anatomical regions of the mandible, which can lead to planning limitations. Purpose: In this study, we propose a 3-D methodology to quantitatively and qualitatively analyze the patient's facial asymmetry and achieve a personalized surgical treatment. Methods: Ninety-nine patients were recruited, only 36 patients met the study's inclusion criteria with a clear indication to ortho surgical treatment and for 3-D planning. Through landmarks in the anatomical structures of interest, the measurements related to intramandibular, middle and upper thirds of the face included the difference of right and left sides in the vertical and horizontal direction in relation to predetermined plans. Results: The clinical characteristics of the study population are: skeletal Class III (94.4%) and prevalence in the initial diagnosis of hemimandibular elongation (72.4%). Moderate correlation was found between condylar height/dif with pogonion position (p-value=0.500) and maxillary canting with ramus height/diff (p-value=0.514). Conclusion: We could not find any relation between the FA pattern and measurements of the three-thirds of the face.